Achieving mental health equity in Black male suicide prevention - Adams, Leslie B.; Thorpe, Roland J. (Frontiers in Public Health, 2023)
Despite a steady decrease in suicide rates in the United States, the rate among Black males has increased in recent decades. Moreover, suicide is now positioned as the third leading cause of death in this population, signaling a public health crisis. Enhancing the ability for future suicide prevention scholars to fully characterize and intervene on suicide risk factors is an emerging health equity priority, yet there is little empirical evidence to robustly investigate the alarming trends in Black male suicide. We present fundamental areas of expansion in suicide prevention research focused on establishing culturally responsive strategies to achieve mental health equity. Notably, we identify gaps in existing research and offer future recommendation to reduce suicide death among Black males. Our perspective aims to present important and innovative solutions for ensuring the inclusion of Black males in need of suicide prevention and intervention efforts.